Etude de l’effet anti-inflammatoire de la Gelée royale « Etude in vivo » - ALEM, Kaouter; BEZZAICH, Aicha (My University, 2023)
Royal Jelly is a naturel substance considered as one of the most important hive products of honey bees, known for its anti-oxidant, anti-diabetic, pharmaceutical properties, which has given it an important place in traditional medicine, and which is currently generating a real interest in new therapeutic formulations. The objective of this study is to assess in vivo the anti-inflammatory activity of Royal Jelly in NMRI mice. The experimental design was supported, determining the carrageenan-induced inflammation. A toxicity test was carried out to examine the toxic and undesirable effects of Royal Jelly. The mice were divided into five groups; the inflammation control group (C-inf), the control group (T) and the royal jelly group at 150 and 300 mg/kg (GR D1, GR D2 respectively) and the standard diclofenac group at 50mg/kg. One hour after intra gastric administration of the different samples, all mice received a single-dose sub plantar injection of 1% carrageen. Determination of the inhibitory effect of Royal Jelly inflammation was determined by measuring the percentage increase in leg volume (%AUG) and the percentage inhibition of leg edema (%INH), followed by a histological examination of the leg tissue. The results indicated that the administration of Royal Jelly at 150 and 300 mg/kg induced a highly and very significant decrease (P<0.01), (P< 0.001) of the percentage increase in leg volume (AUG%) at the 5th and 6th hour of the exam, compared to the inflammation control group (C- inf). In addition, the percentage of inhibition of leg edema (INH %) significantly very high (P 0.01) in mice treated with 150 mg/kg at the 4th and 6th hour, compared to the standard groups. As well as the 300mg/kg dose exposes a significant increase (#P 0.05) from the 4th hour to the 6th hour of experience, compared to the standard groups. The histological study clearly supported the results obtained previously. Indeed, a remarkable restoration of the damaged leg tissue by inflammation was observed in groups treated with Royal Jelly at 150 and 300 mg/kg. These results clearly suggest the attribution of the anti-inflammatory effect of Royal Jelly.
Keywords: Royal jelly; inflammation; anti-inflammatory activity; carrageenan; in vivo